Direct shoulder MR arthrography using an iron-based positive T1 contrast agent (NEMO-103): comparison of image quality with gadolinium-based contrast - Hong Seon Lee; Chan Woong Jang; Young Han Lee; Sungjun Kim; Jung Hyun Park (Scientific Reports)
Abstract The need for alternative MR contrast agents in direct shoulder MR arthrography (MRA) arises from limitations associated with gadolinium-based contrast agents (GBCAs), which are deemed "off-label" for MRA and raise concerns about potential toxicity to joint tissue. This study aims to compare the image quality of NEMO-103 (codename)-based and GBCA-based direct shoulder MRA. A total of 89 MRAs from 81 patients were analyzed, with 39 NEMO-103-based MRAs from 31 patients and 50 GBCA-based MRAs from 50 patients. The MRAs were performed at 3.0-T using fast/turbo spin-echo T1- and T2-weighted images with or without fat suppression (spectral presaturation with inversion recovery). Participants included individuals undergoing MRA for suspected or diagnosed shoulder pathologies between August 2021 and September 2022. Quantitative assessments (contrast-to-noise ratio [CNR] and distension measurements) and qualitative evaluations (distension, sharpness, contrast, and overall image quality scores) were conducted by three musculoskeletal radiologists. A visual Turing test (VTT) was used to assess the ability of 39 clinicians to differentiate between the two contrast agents. Statistical tests included the Shapiro–Wilk test, independent t-tests, and chi-squared test. The study compared 31 NEMO-103-based MRAs (11 females [35.5%], age: 40.0 ± 13.0 years) and 38 GBCA-based MRAs (14 females [36.8%], age: 49.4 ± 18.7 years) within 30 min post-injection, and 8 NEMO-103-based MRAs (3 females [37.5%], age: 38.0 ± 7.8 years) versus 12 GBCA-based MRAs (5 females [41.7%], age: 56.2 ± 15.7 years) in the 30–60-min post-injection timeframe. NEMO-103-based MRAs demonstrated superior axillary pouch distension and overall image quality in both comparisons. CNR was notably higher with NEMO-103. The VTT showed a 53.3% accuracy in differentiating NEMO-103 from GBCA, similar to random guessing. NEMO-103 may serve as a potential alternative to GBCAs for direct shoulder MRA, offering comparable or superior image quality with potentially fewer concerns related to gadolinium-associated toxicity.